Gaya Bahasa Guru Bahasa Inggris Di AMIK Tunas Bangsa Pematangsiantar - susiani, susiani (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2022)
This research is related to the language style used by English Teachers. In these analysis are : “what are the language styles used and what is the most dominant language style used in speaking by English Teachers at AMIK Tunas Bangsa Pematangsiantar. To answer the problem, the writer follows some theories, namely : as Sapir (1921), Chaika (1982), Chambers (1995), Hudson (1986), Joos (1956), Holmes ( 2001 ). The aim of this research is to find out the language style that the teachers use in speaking and what the most dominant language style English Teachers use specially at AMIK Tunas Bangsa Pematangsiantar. The objects of the research is the teachers speaking during the presentating the seminar meeting. To collect the data, the writer record the teachers speaking.